Five Year Plan 1978-83 Andhra Pradesh Draft Outline Vol. II - Planning Commission (Planning Commission, 1978)
About 70% of the people of the State are dependent on Agriculture and there is no likelyhood of any substantial change occurring in this position in the near future. Achievement of full employment in rural areas and removal of poverty are the basic objectives of the Medium Term Plan. Therefore, as the Primary Sector of the economy employing the largest segment of the working population, the highest priority has to be accorded to the development of agriculture in the State during the Plan period.
Finance and Planning Department, Government of Andhra Pradesh